2015
DOI: 10.1055/s-0034-1396261
|View full text |Cite
|
Sign up to set email alerts
|

Berufliche Wiedereingliederung nach Becken- und Azetabulumfrakturen

Abstract: Fractures of the pelvis and the acetabulum currently lead in one of five patients to loss of employment. Thereby the trauma threatens the social security of the young patients. Follow-up care should be intensified to increase recovery rates and reduce the burden of long-term work disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…However, the specific method for quantifying impairment lacks description. Nusser et al added a minimum duration of work absence to their socioeconomic outcome reporting [86]. Several other studies specifically characterized the sustained absence from work into categories such as retired, unemployed, undergoing rehabilitation, recipient of disability payments, in school, never working, or retraining for a different job [85,115].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific method for quantifying impairment lacks description. Nusser et al added a minimum duration of work absence to their socioeconomic outcome reporting [86]. Several other studies specifically characterized the sustained absence from work into categories such as retired, unemployed, undergoing rehabilitation, recipient of disability payments, in school, never working, or retraining for a different job [85,115].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nusser et al [37] on a group of 249 patients with acetabular fracture found that one-third of the subjects lost their ability to return to work within the period of one to two years after completing their physiotherapy. This is potentially a threat to the financial existence of these patients, as well as to their psychological well-being and social integration [37]. The authors agree on the need to provide particularly attentive care and intensive therapeutic programs to those patients who had had acetabular fractures [11,37].…”
Section: Discussionmentioning
confidence: 99%
“…This is potentially a threat to the financial existence of these patients, as well as to their psychological well-being and social integration [37]. The authors agree on the need to provide particularly attentive care and intensive therapeutic programs to those patients who had had acetabular fractures [11,37].…”
Section: Discussionmentioning
confidence: 99%
“…22 In traumatology-and particularly in pelvic ring fractures-surgeons prefer minimally invasive techniques, as minimally invasive surgery allows the patient to return to work sooner. 23,24 Our new bridging plate technique appropriates for all types of pubic symphysis disruption (isolated or with superior ramus fractures) and unilateral or bilateral pubic superior ramus fractures, located medial to the lateral border of the pubic tubercle. When pubic symphysis is disrupted, type II fractures of the superior ramus can also be treated with this technique.…”
Section: Discussionmentioning
confidence: 99%